Efektifitas Penerapan Sistem Merid terhadap Prinsip Keadilan dan Kesetaraan dalam Menejeman PNS - Lasambo, Nurlin; Uswatun Otoluwa, Siti Nur; Moonti, Roy Marthen (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
Theimplementation of the merit system in civil servant management has shown its effectiveness in supporting the principles of justice and equality. However, to achieve more optimal results, efforts are needed to increase the capacity of human resources, strengthen supervision mechanisms, and enforce sanctions for violations. In addition, the government needs to encourage changes in organizational culture to better support the principle of meritocracy. Further studies are needed to evaluate the long-term impact of implementing the merit system at different levels of government. The merit system is a reflection of professional personnel management where the placement of employees and officials uses performance competencies and track records as a measure of appointment. The main purpose of the implementation of the merit system is to improve professionalism, fairness, and equality in the management of Civil Servants (PNS). The purpose of this research is to find out the Effectiveness of the Implementation of the Merid System on the Principles of Justice and Equality in Translating Civil Servants. This paper was carried out with the aim of finding out how the Implementation of the Effectiveness of the Implementation of the Merid System on the Principles of Justice and Equality in Translating Civil Servants by using a qualitative analysis method. so that it is expected to contribute thoughts to the government in the assessment and implementation of Merid Sytem towards a better direction.